Social participation and logistical elements of cemetery waste biofraction management - Kostecka, Joanna; Progorowicz, Sławomir; Mazur-Pączka, Anna; Pączka, Grzegorz; Szura, Renata; Kiryluk, Aleksander; Butt, Kevin R.; Garczyńska, Mariola (Economics and Environment, 2024)
In the 21st century, waste is a growing problem and must be considered one of the essential elements of creating conditions for sustainable development. The article pays special attention to the biofraction of cemetery waste, and interviews with cemetery visitors made a possible determination of its place among other wastes produced in the cemetery. The willingness of cemetery visitors to participate in the logistics of the cemetery waste management system was also tested. The article also presents selected elements of cemetery waste management logistics. The system should consist of several subsystems. Subsystems of waste minimisation "at the source" and waste segregation, disposal, and secondary management were considered crucial. In addition to the logistics mentioned above, subsystems were proposed to include innovation in cemeteries, the biotechnology of composting/vermicomposting of the biofraction, and segregation on-site by those cleaning their graves. The cemetery biofraction represents a waste suitable for on-site management, increasing the potential for environmental, social, and economic savings. The issues under consideration are part of the problem of integrating the cemetery biofraction into the green recycling system in force in Europe. Logistics for management of other cemetery wastes (plastic, metal, glass, and paper), which require subsystems involving their long-distance transportation, should be limited at the level of purchase by cemetery users. From civic participation in the control of logistical improvements, the entire cemetery waste management system will gradually evolve.